2021
DOI: 10.2147/dmso.s304796
|View full text |Cite
|
Sign up to set email alerts
|

Non-Enzymatic Glycation of Transferrin and Diabetes Mellitus

Abstract: Diabetes is a metabolic disease characterized by high blood sugar. Its complications may damage multiple organs, such as eyes, kidneys, heart, blood vessels, and nerves, severely threatening human health. Transferrin (Tf) is a major iron transport protein in the body. Recent studies have shown that the degree of non-enzymatic glycated modification of Tf is increased in diabetic patients, and glycated Tf is closely related to the occurrence and development of diabetes and diabetic complications. However, the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 79 publications
2
5
0
Order By: Relevance
“…Diabetes is a metabolic disease where prolonged high blood sugar levels can lead to various complications. In ophthalmology, diabetes can affect the health of the lens in multiple ways, including accelerating cataract development through promoting nonenzymatic glycation reactions and oxidative stress [16][17][18]. It's reported that the likelihood of cataracts in diabetic patients is five times higher.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes is a metabolic disease where prolonged high blood sugar levels can lead to various complications. In ophthalmology, diabetes can affect the health of the lens in multiple ways, including accelerating cataract development through promoting nonenzymatic glycation reactions and oxidative stress [16][17][18]. It's reported that the likelihood of cataracts in diabetic patients is five times higher.…”
Section: Discussionmentioning
confidence: 99%
“…HK2 [269], PNPLA3 [270], CPB2 [271], SEMA4C [272], LRP2 [273], SLC5A11 [274], F11 [275], ANGPTL2 [276] and CYP2A6 [277] genes might be related to the pathophysiology of autoimmune disease. A recent study revealed that SLAMF7 [278], FCRL3 [279], CCR4 [280], GZMA (granzyme A) [281], CCR2 [282], CD48 [283], CD3E [284], CCL4 [285], FASLG (Fas ligand) [286], SLAMF1 [287], CD28 [288], IL7R [289], UBASH3A [290], CD3D [291], ICOS (inducible T cell costimulator) [292], CCL5 [293], CCL3 [294], LTF (lactotransferrin) [295], CTLA4 [296], TNFRSF9 [253], C6 [297], IL5RA [298], IL2RG [299], NPY2R [300], DRD3 [301], CD52 [302], CD163 [303], IQGAP2 [304], PRPH (peripherin) [305], MSR1 [306], HGF (hepatocyte growth factor) [307], TTR (transthyretin) [308], IL9 [309], ADM (adrenomedullin) [310], ANGPTL4 [311], CHI3L1 [312], CDH1 [313], SREBF1 [314], CDKN1C [315], TSC22D4 [316], CFTR (CF transmembrane conductance regulator) [317], INSIG1 [318], HSD17B3 [319], GREM1 [320], ATF3 [321], HK2 [322], TF (transferrin) [323], GLUL (glutamate-ammonia ligase) [324], DMRT2 [325], FN3K [326], TREH (trehalase) [327], ADAMTS4 [328], BMP2 [329], LMNA (lamin A/C) [330], ERBB3 [331], HSD11B1 [332], DLL1 [333], NKX2-2 [334], FGF11 [335], ASPA (aspartoacylase) [336], FASN (fatty acid synthase) [337], PNPLA3 [338], ADORA1 [339], WNT7A [340…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on serum early-glycated proteins predominantly focused on individual high-abundance proteins, such as glycated hemoglobin, glycated albumin, and glycated transferrin [ 15 , 25 , 26 ]. In contrast, our advanced proteomics platform allows for the detection of both highly abundant and low-abundance glycated proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Detecting early-stage glycation is vital for early monitoring and better intervention in aging-related deterioration [10] . Some well-known early-stage glycated markers, such as glycated hemoglobin and glycated albumin, have been utilized as indicators for blood glucose control monitoring, while early-stage glycated transferrin shows potential for monitoring blood glucose control and early diagnosis of diabetic nephropathy [ 15 , 20 , 21 ]. These findings underscore the importance of studying early-stage glycated proteins in biological processes.…”
Section: Introductionmentioning
confidence: 99%